Sensitivity of dynamic behaviour of the FE model: Case study for the ignalina NPP reactor building - Baušys, Romualdas; Dundulis, Gintautas; Kačianauskas, Rimantas; Markauskas, Darius; Rimkevičius, Sigitas; Stupak, Eugeniuš; Stupak, Stanislav; Šliaupa, Saulius (Journal of Civil Engineering and Management, 2008)
The 3D thin‐walled finite element model of Ignalina NPP Unit 2 reactor building was developed aimed at the evaluation of the global dynamic behaviour with a focus on the seismic response. The model comprises description of the monolithic structures, while prefabricated frame structures are ignored and replaced by external masses. Sensitivity study of the selected dynamic characteristics of the model with respect to data uncertainties is considered. Uncertainty of the model is considered in terms of masses of removed structures and wall stiffness. Seismic input is represented by the site specific free‐field ground response acceleration spectra. The sensitivity study concerns variations of frequencies and acceleration of in‐structure horizontal response spectra at specified points. Maximal bending moments are also considered. It was obtained that the reactor level is not sensitive to the uncertainties considered, while discernable sensitivity was detected at the top level of the structure.Ignalinos AE reaktoriaus pastato dinaminio BEM modelio jautrumo analizėSantraukaю Pateikta Ignalinos atominės elektrinės pastato erdvinio baigtinių elementų dinaminio modelio kūrimo koncepcija, išnagrinėtas šio modelio jautrumas keičiamoms masėms ir sienų standumui. Parodyta, kaip šie keičiami dydžiai turi įtaką dažniams, horizontaliems tam tikrų nagrinėjamų taškų atsako spektrams, lenkimo momentų persiskirstymui ir jų didžiui.Reikšminiai žodžiai: Ignalinos AE, baigtinių elementų modelis, savųjų dažnių ir seisminė analizė, plyno lauko spektras, atsako spektras.First Published Online: 14 Oct 2010